Exposure to volatile organic compounds and airway inflammation - Kwon, Jae-Woo; Park, Hee-Won; Kim, Woo Jin; Kim, Man-Goo; Lee, Seung-Joon (Environmental health, 2018)
Exposure to low levels of volatile organic compounds (VOCs) in ordinary life is suspected to be related to oxidative stress and decreased lung function. This study evaluated whether exposure to ambient VOCs in indoor air affects airway inflammation. Thirty-four subjects from the hospital that had moved to a new building were enrolled. Symptoms of sick building syndrome, pulmonary function tests, and fractional exhaled nitric oxide (FeNO) were evaluated, and random urine samples were collected 1 week before and after the move. Urine samples were analyzed for VOC metabolites, oxidative stress biomarkers, and urinary leukotriene E4 (uLTE4) levels. The level of indoor VOCs in the new building was higher than that in the old building. Symptoms of eye dryness and eye irritation, as well as the level of a xylene metabolite (o-methylhippuric acid) increased after moving into the new building (p = 0.012, p = 0.008, and p < 0.0001, respectively). For the inflammatory markers, FeNO decreased (p = 0.012 and p = 0.04, respectively) and the uLTE4 level increased (p = 0.005) after the move. Exposure to a higher level of VOCs in everyday life could affect airway inflammation.